2013
DOI: 10.1152/ajpcell.00069.2012
|View full text |Cite
|
Sign up to set email alerts
|

Role of TRPM2 in cell proliferation and susceptibility to oxidative stress

Abstract: The transient receptor potential (TRP) channel TRPM2 is an ion channel that modulates cell survival. We report here that full-length (TRPM2-L) and short (TRPM2-S) isoform expression was significantly increased in human neuroblastoma compared with adrenal gland. To differentiate the roles of TRPM2-L and TRPM2-S in cell proliferation and survival, we established neuroblastoma SH-SY5Y cell lines stably expressing either TRPM2 isoform or empty vector. Cells expressing TRPM2-S showed significantly enhanced prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(83 citation statements)
references
References 89 publications
(110 reference statements)
6
77
0
Order By: Relevance
“…The decreased proliferation of untreated SK-N-DZ and SK-N-FI cells expressing TRPM2-S (Fig. 11A) may be due to reduced calcium influx leading to lower levels of mitochondrial proteins including HIF-1/2␣ and mitochondrial function, as shown for SH-SY5Y cells expressing TRPM2-S (40,41).…”
Section: Trpm2 Depletion Inhibits Mitochondrial Function and Survivalmentioning
confidence: 83%
See 3 more Smart Citations
“…The decreased proliferation of untreated SK-N-DZ and SK-N-FI cells expressing TRPM2-S (Fig. 11A) may be due to reduced calcium influx leading to lower levels of mitochondrial proteins including HIF-1/2␣ and mitochondrial function, as shown for SH-SY5Y cells expressing TRPM2-S (40,41).…”
Section: Trpm2 Depletion Inhibits Mitochondrial Function and Survivalmentioning
confidence: 83%
“…TRPM2 has an important role in cell survival following oxidative stress or ischemic injury (35)(36)(37)40). Recent studies have shown that TRPM2 is highly expressed in a number of malignancies including melanoma, lung, neuroblastoma, and breast cancer (39,41,42), suggesting that it plays a role in promoting tumor growth, and that inhibition may be a novel therapeutic approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It becomes clear that increases in cellular ROS levels are known to be associated with aging [70][71][72][73][74][75] . Increased cellular oxidative stress regulates FoxO post-translational modifications and the activation of the FoxO family has been shown to regulate cellular oxidative-stress resistance [76][77][78][79][80][81] . Interestingly, to support these findings, recent studies suggest a possibility that Sirt3 and FoxO3a have been linked to an extended life span in humans [75][76][77][78]82] .…”
Section: Longevitymentioning
confidence: 99%